2017
DOI: 10.3390/coatings7070096
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of PEDOT/PSS/Chitosan-Coated Electrodes for Electrochemical Bio-Sensing

Abstract: Poly(3,4-ethylenedioxythiophene) (PEDOT) doped with poly (styrene sulfonate) (PSS) has a variety of chemical and biomedical applications. Additionally, chitosan has been extensively used in industrial and medical fields. However, whether chitosan could be incorporated into conducting polymers of PEDOT/PSS is not clear. In this study, the PEDOT/PSS/chitosan coatings were electrochemically polymerized on the surface of 0.5 mm platinum (Pt) electrodes and the properties of electrochemical cyclic voltammetry (CV) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…Researchers found that MXene nanosheets could be potential supporting materials due to the large surface area, and other nanomaterials used in the decoration of MXene sheets can effectively solve the interlayer aggregation and application in electrochemical sensors [ 23 , 24 ]. Chitosan (CS) is one of the natural amino polysaccharides which have an excellent film-forming ability, and are cost effective, environmentally friendly, and biocompatible [ 25 , 26 ]. Although CS cannot conduct electricity, it is often used in electrochemical sensors because of its excellent property of biocompatibility and film-forming ability.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers found that MXene nanosheets could be potential supporting materials due to the large surface area, and other nanomaterials used in the decoration of MXene sheets can effectively solve the interlayer aggregation and application in electrochemical sensors [ 23 , 24 ]. Chitosan (CS) is one of the natural amino polysaccharides which have an excellent film-forming ability, and are cost effective, environmentally friendly, and biocompatible [ 25 , 26 ]. Although CS cannot conduct electricity, it is often used in electrochemical sensors because of its excellent property of biocompatibility and film-forming ability.…”
Section: Introductionmentioning
confidence: 99%
“…Polylactic acid (PLA) has been regarded as the most promising sustainable and biodegradable fiber to replace conventional polyethylene terephthalate (PET) polyester fiber in textile products. It is also widely used in medical and health, agriculture and forestry protection, and packaging materials due to its good physical and mechanical properties, excellent biocompatibility, and natural degradation [1][2][3]. However, there are still some disadvantages in the properties of PLA materials, such as high inertia, poor hydrophilicity and difficulty to react with other substances, which greatly limit the further development of PLA in the field of biomedical functional materials [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Doping mechanisms involve reduction states that are not stable in air. Therefore, there is currently major scientific interest in the search for a stable n-type conducting polymer for the manufacture of thermoelectric modules . Intrinsically conducting polymers (ICPs) are attracting widespread attention due to their promise in organic light-emitting diodes (OLEDs), , organic solar cells (OSC), , supercapacitors, and thermoelectric devices. , They exhibit several desirable properties, including flexibility, low cost, ease of chemical modification, and flexible processing, which render them a viable alternative to inorganic semiconductors. Thin ICP films are being used as coatings also for corrosion protection as well as electromagnetic shields, radar absorbers, sensors, , and polymeric actuators . There has been an ever increasing number of scientific studies dedicated to these topics in recent years …”
Section: Introductionmentioning
confidence: 99%
“…The maximum thermoelectric efficiency is obtained when doping levels are optimized to produce the maximum power factor (= S 2 σ) and the minimum thermal conductivity. Generally, electrical conductivity increases when the Seebeck coefficient decreases, ,, , while it is known that nanostructuration of a material improves the Seebeck coefficient by phonon scattering which reduces thermal conductivity. ,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation